Electron Microscopic Ultra Structural Study of Alteration in Leukocytes of Patients Having Leukemia Disease - Abdulhadi L; Haitham (Sharwes Scientific Journal, 2022)
This study was design to put a light on the ultra-structural changes in leukocyte of patient having leukemia disease. The result demonstrates a presence of immature leukocyte with several changes in their structure besides adherence phenomena in group of leukocyte cells was seen. Most studies reported in 2020 showed a positive association between uranium exposure and adverse health outcomes.